Maturity Curves And Harvest Schedule Recommendations For CP Sugarcane Varieties - Robert A. Gilbert; James M. Shine, Jr.; Jimmy D. Miller; Ronald W. Rice; Curtis R. Rainbolt (EDIS)
SS-AGR-221 is a publication of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published April 2004.